Potorono Village Fund Management on Community Satisfaction in the View of Islamic Economics - Erwin Shofiyanti (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: Various kinds of government efforts were made to facilitate protect and all various norms in order to improve and fulfill the needs of Indonesian society, but poverty have not weakened but increasing. One form of government effort is the division of administrative areas to able control and fulfillment of needs according to ideals. In this study the author will examine the management of Potorono village funds on community satisfaction and Islamic review about it.Design/Method/Approach: The researcher used a qualitative descriptive method which is field type with a sample consisting of interviews with the government and also a questionnaire from the community totaling 60 samples.Findings: The results indicate that the community is satisfied because it has run the government well and effectively both in terms of quality and service.Originality/Values: Likewise, in the view of Islamic economics, it is also considered appropriate because it has applied the role of the prophet Muhammad SAW. Siddiq, Amanah, Tabligh and Fathonah.